The Topological Indices of Coprime Graph for Integer Module Group - Abdurahim, Abdurahim; Awanis, Zata Yumni; Syechah, Bulqis Nebulla; Syaharuddin, Syaharuddin (JURNAL DIFERENSIAL, 2024)
This study delves into the fascinating realm of coprime graphs within the integer modulo group, revealing a fundamental property where these graphs manifest as star graphs when the order corresponds to a prime power. This pivotal insight, as elucidated by [1], plays a crucial role in the determination of topological indices for these graphs. The research culminates in the formulation of formulas for the First Zagreb index and the Second index of coprime graphs in the context of integer modulo groups, unveiled in the last two theorems. These numerical topological indices are poised to unveil intricate correlations among group elements, contingent upon their order, echoing the foundational principles of chemical graph theory. This exploration not only enriches our understanding of group structu.Coprime Graph